Perceived physical literacy instruments for sports club coaches: further differentiated validation - Jiangping Fu; Weiping Zhang; Bing Cao; Huiling Yu; Huiling Yu; Hua Li (Frontiers in Psychology, 2025)
BackgroundThe concept of physical literacy (PL) is a theoretical basis for public health. China has proposed PL indicators in its 2030 Sports Power Strategy through systematic administrative measures. Sports club coaches are an important force in promoting public health, and their PL is worthy of attention. The objective is to assess the factor structure of the Perceived PL Instrument (PPLI) in Simplified Chinese for sports club coaches.MethodsThe 18-item PPLI was selected because of its efficiency and effectiveness for physical education teachers. The research team translated the questionnaire (English–Simplified Chinese). The questionnaire was distributed to coaches of school sports clubs and social sports clubs. The factor structure was established by exploratory factor analysis and confirmatory factor analysis (CFA).ResultsThe factor structure was a 4-factor, 9-item scale with satisfactory validity. Through exploratory factor analysis, item loadings ranged from 0.70 to 0.75 (Cronbach’s α, 0.83–0.87). Through CFA, factor loadings ranged from 0.78 to 0.86.ConclusionThe PPLI can be used as a reliable and valid instrument to test the PL of sports club coaches.